Immigration and Globalization: A Review Essay - Borjas, George J. (Journal of Economic Literature, 2015)
This essay revisits the argument that the removal of worldwide immigration restrictions would induce a very large increase in world GDP. The recent books Exodus: How Migration is Changing Our World by Paul Collier and The Price of Rights: Regulating International Labor Migration by Martin Ruhs raise a number of questions about the underlying economic model. The essay shows how these concerns can greatly attenuate the predicted gains. (JEL F22, F66, J11, J18, J61)